Improving Efficiency in Construction Projects through Utilization of BIM Technology in Construction Project Management - Unbara, Lindawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
The research method uses a quantitative approach with a population of construction companies that have implemented BIM, and the sample consists of staff and project managers selected by purposive sampling of 100 respondents. The data used is primary and secondary data with data collection techniques via online questionnaires which are analyzed using Pearson correlation analysis and multiple linear regression. The research results show that BIM adoption and supporting factors such as training, infrastructure, and management support have a significant effect on project efficiency, so these findings support broader BIM implementation and improving supporting factors as a strategy to increase efficiency in construction projects. Therefore, it is recommended that construction companies increase investment in BIM technology as well as training and infrastructure support to maximize project efficiency benefits.